Negative bias in encoding and recall memory in depressed patients with inadequate response to antidepressant medication. - Ramli, Fitri Fareez; Singh, Nisha; Villa, Luca M.; Waters, Shona; Harmer, Catherine J.; Cowen, Philip J.; Godlewska, Beata R. (Psychopharmacology, 2026)
Rationale: Cognitive theories propose that negative biases in emotional processing contribute to the maintenance of depressive states. Previous studies reported that acute antidepressant treatment in depressed patients reversed negative emotional biases. However, studies addressing the differences in emotional processing between healthy volunteers and clinically depressed patients with inadequate response to standard antidepressant treatments are limited. Objectives: To investigate the differences in emotional processing domains between depressed patients with inadequate response to current antidepressant treatment and healthy controls. Methods: Fifty-four medicated patients with major depression and 45 age- and sex-equated healthy volunteers were tested using the Oxford Emotional Testing Battery. Results: There was no difference between the two groups in the accuracy of recognising emotional facial expressions. However, there was a significant difference in the pattern of response times in an emotional categorisation task (F1,97 = 6.44, p = 0.013, partial η2 = 0.017) where healthy controls had faster responses towards positive than negative self-referent words (95%CI: -0.291 – -0.054, p = 0.005). In contrast, patients had no significant differences in reaction time for categorizing positive and negative self-referent descriptors. There was also a significant group interaction in an emotional memory task (F1,91 = 7.90, p = 0.006, partial η2 = 0.080) where healthy volunteers recalled significantly more positively valenced words than depressed patients (95%CI: -2.104 – -0.168, p = 0.022). Conclusions: Depressed patients with inadequate responses toward antidepressants had negative biases in emotional categorisation and emotional memory. These psychological abnormalities may represent targets for treatment in patients with difficult-to-treat depression.